Still getting it on online: Thirty years of queer male spaces brokered through digital technologies. Issue 11 (6th September 2018) - Miles, Sam
Abstract: Research across the social sciences testifies to an ongoing relationship between queerness and digital technology. This article tracks how different online spaces for queer men have changed as the internet has developed over the past 30 years. It argues that queer spaces have become increasingly dominated by, and predicated on, internet technology. I review early interpretations of cyberspace as a liberatory space freed from heteronormativity and later more critical assessments of its potential, positioning arguments for and against the internet's status as a protective space. I then evaluate the huge popularity of mobile phone‐based dating and hook‐up apps such as Grindr and Tinder. These platforms have developed from static desktop offerings including Gaydar and PlanetRomeo, but emphasise a distinctly hybridised socio‐technical experience in partner seeking. Finally, I consider the impact of locative media on more traditional queer concepts of cruising and community, concluding that contemporary apps refigure both structures in distinctive ways reflecting larger changes in sexuality and space studies.